Curriculum management through the Mangunwijaya Curriculum Tree in primary education - Faizah Nadela; Slamet Lestari (Universitas Pendidikan Indonesia, 2025)
Curriculum management plays a crucial role in ensuring that primary education provides children with meaningful learning experiences. In Indonesia, challenges in curriculum governance often arise from top-down approaches and limited teacher participation, which reduce the relevance of learning to students’ real-life contexts. This study aims to analyze how curriculum management at Mangunan Experimental Primary School addresses these issues by applying Y.B. Mangunwijaya’s humanistic philosophy through the Pohon Kurikulum Mangunwijaya (PKM) or Mangunwijaya Curriculum Tree. The research employed a qualitative case study design to gain a comprehensive understanding of curriculum planning, implementation, and evaluation. Data were collected from principals, teachers, curriculum coordinators, and the Educational Development Laboratory through in-depth interviews, participant observation, and document analysis, with triangulation of sources and methods to ensure validity. The findings indicate that curriculum planning is participatory, conducted through foundation and school-level workshops guided by the Understanding by Design framework and the integration of seven child capacities. Implementation emphasizes inquiry-based and contextual learning supported by distinctive programs, while evaluation combines narrative classroom assessments withs systematic supervision. PKM thus illustrates curriculum management as a participatory and humanistic process that fosters holistic student development. Abstrak Manajemen kurikulum memiliki peran penting dalam memastikan pendidikan dasar mampu memberikan pengalaman belajar yang bermakna bagi anak. Di Indonesia, tata kelola kurikulum kerap menghadapi kendala akibat pendekatan yang bersifat top-down dan keterlibatan guru yang terbatas, sehingga mengurangi relevansi pembelajaran dengan konteks kehidupan nyata peserta didik. Penelitian ini bertujuan untuk menganalisis bagaimana manajemen kurikulum di SD Eksperimental Mangunan mengatasi permasalahan tersebut melalui penerapan filosofi humanistik Y.B. Mangunwijaya yang diwujudkan dalam Pohon Kurikulum Mangunwijaya (PKM). Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus untuk memperoleh pemahaman mendalam mengenai perencanaan, pelaksanaan, dan evaluasi kurikulum. Data dikumpulkan dari kepala sekolah, guru, koordinator kurikulum, dan tim Laboratorium Pendidikan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen, dengan triangulasi sumber dan teknik untuk menjaga validitas. Hasil penelitian menunjukkan bahwa perencanaan dilakukan secara partisipatif melalui lokakarya di tingkat yayasan dan sekolah dengan pendekatan Understanding by Design serta integrasi tujuh modal dasar anak. Pelaksanaan menekankan pembelajaran kontekstual dan berbasis inkuiri melalui program khas, sementara evaluasi menggabungkan asesmen naratif di kelas dengan supervisi sistematis. PKM mencerminkan manajemen kurikulum sebagai proses partisipatif dan humanistik yang mendorong perkembangan murid secara holistik. Kata Kunci: kurikulum humanis; manajemen kurikulum; pendidikan sekolah dasar; PKM; Pohon Kurikulum Mangunwijaya